Using the Health Belief Model to identify communication needs in the male circumcision campaigns to prevent HIV/AIDS in Siaya County of Kenya - Otteng, Osir; Wenje, Peres; Kiptoo, Michael; Anyonje, Lydia; Mwangi, Moses (Advances in Social Sciences Research Journal, 2020)
Behaviour change communication experts consider individual beliefs vital to identifying communication needs in healthcare programmes. This study examined the use of four constructs of the health belief model, viz. the belief that a person is vulnerable to a disease, and that the disease is severe; and the belief that an intervention against the disease has benefits and that there are barriers to adopting that intervention, as the basis for developing communication strategies in the implementation of the voluntary medical male circumcision (VMMC) programme for prevention of HIV/AIDS in Siaya county of Kenya. A structured questionnaire was administered on 350 male residents of the county aged between 18 and 50 years selected using the snowball sampling techniques. Qualitative data were collected through two focus groups discussions involving five men and five women residents. The study found that the residents of Siaya, particularly those living along the shores of Lake Victoria, believe that, because of their occupation and lifestyle, they are susceptible to HIV, the same way they perceive the disease as severe. The best known benefit of VMMC among the residents is its ability to reduce a man’s chances of contracting HIV. Other benefits, such as prevention of sex-related diseases among women are largely obscure. There are specific barriers to VMMC such as apprehension over pain and disruption of economic engagements. The study concurs that the health belief model is crucial for the development of audience-focused health communication and recommends its use in VMMC programme to produce targeted messages for different audience segments.